The work effort, self-esteem and mental health in working women in Metropolitan Lima - Loli Pineda, Alejandro (2014)
Many people and researchers have expressed concern about the mental and physical health of women working outside the home, it is argued that the diversity of roles and the hours spent at work entail damage. In this regard there are many researches, but the researchers found what they are looking for. Thus, few articles have been published regarding protective factors; therefore, the objective of this chapter is to look at the two sides. A survey was administered to 292 Peruvian women to observe the correlations between the imbalance, effort and reward, the physical and mental health, self -esteem, self-efficacy, distress, and family integration. Consisted of five groups: only housewives, housewives some extra income (babysitting, washing, ironing, selling items among family and friends, etc.), Housewives and professionals, employed no household responsibilities , and home professionals without liability. In general, the latter group showed better scores on the variables included, while only dedicated women had the lowest scores. One conclusion: the multiple roles do not necessarily mean physical and mental health deteriorated. Additional research is suggested.